Primary Posterior Sagittal Anorectoplasty and Repair of Esophageal Atresia with Tracheoesophageal Fistula in the Same Sitting - Hasan, Zaheer; Thakur, Vinit Kumar; Kumar, Vijaendra; Yadav, Ramdhani; Rahul, Sandeep Kumar (Journal of Neonatal Surgery, 2018)
Esophageal atresia and tracheoesophageal fistula is often associated with anorectal malformation. Traditionally, staged surgeries are performed in this condition. We did a successful repair of esophageal atresia and tracheoesophageal fistula and primary posterior sagittal anorectoplasty for anorectal malformation in the same sitting.